2019
DOI: 10.1111/pbr.12688
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of haploid male fertility in maize (Zea mays L.)

Abstract: Haploid genome doubling is a key limiting step of haploid breeding in maize. Spontaneous restoration of haploid male fertility (HMF) provides a more promising method than the artificial doubling process. To reveal the genetic basis of HMF, haploids were obtained from the offspring of 285 F2:3 families, derived from the cross Zheng58 × K22. The F2:3 families were used as the female donor and Yu high inducer No. 1 (YHI‐1) as the male inducer line. The rates of HMF from each family line were evaluated at two fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 29 publications
(45 reference statements)
4
25
0
Order By: Relevance
“…Fifteen lines were identified as exhibiting high SHGD, and among those, 14 single nucleotide polymorphisms (SNPs) were identified as significantly contributing to HMF (Figure 2). One of these SNPs may correspond to qhmf2 identified in the study by Ren et al [23], as well as qHMF3c identified by Yang et al [38] on chromosome 3 (Figure 2).…”
Section: Genetic Architecture and Candidate Genes Of Spontaneous Haplmentioning
confidence: 72%
See 4 more Smart Citations
“…Fifteen lines were identified as exhibiting high SHGD, and among those, 14 single nucleotide polymorphisms (SNPs) were identified as significantly contributing to HMF (Figure 2). One of these SNPs may correspond to qhmf2 identified in the study by Ren et al [23], as well as qHMF3c identified by Yang et al [38] on chromosome 3 (Figure 2).…”
Section: Genetic Architecture and Candidate Genes Of Spontaneous Haplmentioning
confidence: 72%
“…Ren et al [23] were the first to report a mapping study for SHGD, where they mapped a large-effect QTL (qhmf4) based on segregation distortion to a region on chromosome 6 in a bi-parental population derived from Chinese germplasm ( Figure 2). Moreover, in Chinese germplasm, Yang et al [38] mapped nine QTL in total ( Figure 2), one of which was located in bin 3.05 on chromosome 3 near qhmf2 described by Ren et al [23], and three QTL in bins 7.01 and 7.02 flanked a significant SNP on chromosome 7 ( Figure 2) that was identified by Chaikam et al [34]. Using a similar approach to [23], Ren et al [21] mapped a large-effect QTL (qshgd1) to chromosome 5 in US-derived germplasm, and a small-effect QTL (qshgd2) to chromosome 6, which mapped to a different location than qhmf4 ( Figure 2).…”
Section: Genetic Architecture and Candidate Genes Of Spontaneous Haplmentioning
confidence: 99%
See 3 more Smart Citations